2017
DOI: 10.1007/s00894-017-3457-y
|View full text |Cite
|
Sign up to set email alerts
|

The permeability enhancing mechanism of menthol on skin lipids: a molecular dynamics simulation study

Abstract: The stratum corneum (SC), the outermost layer of skin, represents the primary barrier to molecules penetrating the skin. Menthol is widely used in clinical medicine as a penetration enhancer due to its high efficiency and relative safety. In this study, molecular dynamics simulations have been performed to investigate the effect of menthol molecules on the structural and permeability of both single component and ternary mixed bilayers. The lipid matrix is modeled as pure ceramide (CER2) or as a 2:2:1 mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…We showed that levomenthol increased the permeation of Mg ++ across porcine skin substantially. This is consistent with earlier data indicating that menthol has penetration enhancing properties [5,6]. However, the increase in Mg ++ skin permeability was not evident during the first hours in this experimental model, indicating that in clinical use Mg ++ -levomenthol cream should be applied on skin on regular basis to obtain any meaningful absorption.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We showed that levomenthol increased the permeation of Mg ++ across porcine skin substantially. This is consistent with earlier data indicating that menthol has penetration enhancing properties [5,6]. However, the increase in Mg ++ skin permeability was not evident during the first hours in this experimental model, indicating that in clinical use Mg ++ -levomenthol cream should be applied on skin on regular basis to obtain any meaningful absorption.…”
Section: Discussionsupporting
confidence: 92%
“…The permeability of the skin can be increased by the excipients termed permeation enhancers. Menthol is one compound with penetrationenhancing properties [5]. Menthol is a natural fat-soluble terpene that can permeate the epidermis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a penetration reagent, menthol has an excellent affinity for the hydrophobic lipid tails. The presence of menthol proved to improve the permeability of the cell membrane by interacting with lipids directly, perturbing the lipid tails to varying degrees . We hypothesized that the hydrophobic DESs could first act on the outer membrane, and thus, destabilize its structure.…”
Section: Resultsmentioning
confidence: 99%
“…This allows two interpretations: the microtubule elimination could act upstream and release a cellular response leading to a unspecific permeabilization of the membrane, or, inversely, menthone/ isomenthone could lead to a permeabilization of the membrane that would kill the cells and, secondarily, cause a breakdown of microtubules. There are several arguments against the second scenario: first, the biological effect is specific with respect to structure: the structurally closely related menthol is much less effective as compared to menthone/isomenthone (Figures 3, 4, and 6), although it is very efficient as membrane permeabilizer (Wang and Meng, 2017). Along the same line, menthone/isomenthone is effective at lower dosage in BY-2 cells overexpressing the TuB6-GFP marker as compared to the non-transformed WT ( Figure 4C) which speaks against unspecific membrane permeabilization as primary cause for microtubule elimination.…”
Section: Discussionmentioning
confidence: 99%